Model Pemberdayaan Usaha Mikro Dan Pengaruhnya Terhadap Kemandirian Usaha - Hamid, Mudasetia; Widyayanti, Evy Rosalina (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
Yogyakarta is a city and the capital of Yogyakarta Special Region in Java, Indonesia. It is renowned as a center of tourism, education and culture. Yogyakarta is one of the foremost cultural centers of Java. This region is located at the foot of the active merapi vulcano. Yogyakarta is often called the main gateway to the Central Java as where it is geographically located. It stretches from Mount Merapi to the Indian Ocean. This province is one of the most densely populated areas of Indonesia. Yogyakarta is popular tourist destination in indonesia after Bali. These have attracted large number of visitors from across Indonesia and abroad to the city. This status makes Yogyakarta is one of the most heterogeneus cities in Indonesia. In edition, Yogyakarta has attracted large number of people to reside in this city for business. One of these comers is small entrepreneurs with their market munchies enterprise (specially a traditional snack trader). This business is one of famous business in Yogyakarta, we will find rows of pavement vendors selling market munchies. The students and tourists are their main target customers. Market munchies enterprise is part of small and medium enterprises SMEs as livelihood activities. SMEs has an important role in economic growth of Indonesia. Therefore, it is very important to develop and strengthen the micro enterprise empowerment. Micro enterprise empowerment is one of strategy to reduce the poverty rate in Indonesia. Major challenger in implement this program are that micro entrepreneurs are conventional and have satisfied with their revenue. It is very important to develop a comprehensive and sustainable micro enterprise empowerment which consist of strengthen the quality of human resources, maximize the government’s roles, empower the enterprise capital and strengthen the partnership and autonomous. Micro enterprise autonomy will contribute to the economic and investment climate. This will lead to establish an accountable enterprise both for the micro enterprise and customers which at the end will strengthen the development of the micro enterprise in Yogyakarta.Keyword: micro entreprise, human resources, government roles, capital, partnership and autonomous.